A proposed community sports and recreation program for children and youth in Bagong Pag-Asa, Quezon City - Lagdamen, Lilia S. 1928-
This proposed program is intended for the youth of ages 7 to 21 in Bagong Pagasa, Quezon City, with the school as the community recreation center. The program aims to provide alternatives to channel youthful energies into more constructive endeavors and to develop their wholesome personalities to become happy and useful members of society. The study surveyed the sports and recreation preferences of the youth as well as the perception of the key people in Bagong Pagasa to estimate the sports and recreation needs of the community. It further measured the correlation of the two sets of responses.
Mimeographed.
Thesis (M.Ed.)--University of the Philippines, Quezon City.
Vita.
Keywords: Community centers -- Philippines; Recreation -- Philippines; Youth centers -- Philippines; Quezon City; Quezon City; Quezon City; Bagong Pag-Asa (Quezon City).